Climate-driven changes in underwater irradiance and primary productivity in an Antarctic fjord (Potter Cove, Western Antarctic Peninsula) - Deregibus, Dolores (2025)
The West Antarctic Peninsula (WAP) is a hotspot of climate warming, evidencing glacier retreat and a decrease in the fast-ice duration. This study provides a > 30-y time-series (1987–2022) on annual and seasonal air temperatures in Potter Cove (Isla 25 de Mayo/King George Island). It investigates the interaction between warming, glacial melt, fast-ice and the underwater conditions (light, salinity, temperature, turbidity) over a period of 10 years along the fjord axis (2010–2019), and for the first time provides a unique continuous underwater irradiance time series over 5 years (2014–2018). The effects on the annual light budget in the water column were studied along the fjord axis in three areas, a low glacier influence area (LGI), an intermediate glacier influence area (IGI), and a high glacier influence area (HGI). To determine the possible impact of light limitation on the viability of benthic primary producers, the minimum annual light requirements and the daily metabolic carbon balance of two key macroalgal Antarctic species, Himantothallus grandifolius and Palmaria decipiens, were estimated. The mean annual, autumn, winter and spring air temperature has risen during the last three decades, but summer temperatures kept rather stable. Turbidity caused by glacial melt mostly governs the underwater light climate while fast-ice duration is currently of minor importance for the annual light budget. Glacier melting differentially affected the fjord system along its axis. The three areas showed quantitative differences in turbidity and underwater irradiance varying across seasons and years. Water clarity significantly decreased within the last few years, with key macroalgal species probably not reaching their minimum annual light requirements during warmer years. This may have considerable effects on the primary productivity of the ecosystem.